Cytologic features and immunohistochemical findings of epithelioid hemangioendothelioma (EHE) in effusion: A case series. Issue 1 (14th August 2020) - Jebastin Thangaiah, Judith; Hanley, Kelly; Nomani, Laila; Policarpio‐Nicolas, Maria Luisa
Abstract: Background: Epithelioid hemangioendothelioma (EHE) is a rare malignant vascular tumor characterized by WWTR1‐CAMTA1, t (1:3) (p36;q25) translocation in 90% of cases. Without prior EHE history, it can mimic other malignant effusions. Recently, CAMTA1 was published as an excellent immunohistochemical surrogate marker for molecular testing for WWTR1‐CAMTA1 fusion in surgical specimens. Methods: A 6‐year retrospective search using our computer system was performed for cases diagnosed as EHE on effusion cytology and surgical specimens. The clinical presentation, cytologic findings and immunohistochemical stain results, including CAMTA1 were reviewed. Results: Four pleural and one peritoneal effusions were identified. The median age was 52 years with a female to male ratio of 3:2. Most patients presented with pulmonary symptoms. The cytologic features were non‐specific easily mimicking other malignancies; especially in the absence of known prior malignancy. This was exemplified by one of our cases which was initially misdiagnosed as adenocarcinoma. Intracytoplasmic erythrocytes were present only on the cell blocks but not on cytology. The cytology cell blocks from patients with prior EHE confirmed on surgical biopsies stained positive for vascular markers (CD31, ERG) and CAMTA1. Conclusion: The features of EHE in effusion are non‐specific and a diagnostic pitfall in cytology. In the absence of prior EHE diagnosis, inclusion of this entity in the differential diagnoses and application of immunohistochemical stain panels will be prudent in avoiding a misdiagnosis. However, in cases with prior EHE diagnosis, CAMTA1 could serve as diagnostic marker; especially on limited cytology material. Additional studies will be helpful in supporting our results.